Computational fluid dynamics of flooding, loading and fully dispersed regime in gas-liquid stirred tank - Nurul Aida, Jamaluddin (2012)
The main aim of this work is to perform computational fluid dynamics on gas-liquid stirred tank operating under flooding,loading and fully dispersed regime.This computational method was conducting with the combination of computational fluid dynamics(CFD)fand drag model changes by using standard FLUENT model.This current work was attempted to predict the gas hold-up and gassed power number similarly like the result obtained by Ford et al.(2008)The overall research methodology consists of two main steps.First step is about drawing the gas-liquid stirred tank geometric and set the set-up and for the second step is about analysis the flow in gas-liquid stirred tank.After the boundary and the tank geometry have been set up,the selected mathematical model were employed in the multiphase model,Eulerian-Eulerian model has been used while in turbulence model, twophase standard k-ε has been employed.Besides that,the drag model of bubble by Schiller & Naumann(1935)was carried out. Diameter of bubbles is taken into account by employed the equation of Sauter mean diameter proposed by Calderbank (1958).The gassed power number and gas hold-up inside gas-liquid stirred tank were found to be in fair agreement to the experimental data adopted from Ford et al.(2008).The advantages of this computational method are the operating cost is lower compared to experimental method and besides, it can reduce the time taken to evaluate the performance of gas-liquid STR by neglecting the prototype‘s design.Through this study,CFD model may be useful to eliminate the impeller flooding in gas-liquid STR.